Molar-Incisor Hypomineralization in Permanent Teeth: Literature Review (Research, Society and Development, 2020)
Molar-Incisor Hypomineralization (HMI) is a terminology described to determine the Enamel Development Defects (DDE), caused during the maturation stage, characterized by qualitative defects, with a systemic etiology that can affect only one permanent molar or, also, the four molars. It is often associated with changes in permanent incisors, which are also affected. The prevalence, etiology and treatment of IMH are still not well defined. Thus, this study aimed to analyze the prevalence, etiology and treatment of Molar-Incisor Hypomineralization (HMI) in permanent teeth. For its development, a bibliographic survey was carried out in the following online databases, such as BVSalud, SCielo and Lilacs, employing 26 studies, which demonstrated the value of early diagnosis and adequate therapy in cases of Molar-Incisor Hypomineralization. Thus, it is concluded that the prevalence can be considered relatively high, for a theme not much reported in the literature. In addition, it is noted that there is a relationship between HMI and health problems in the first years of life, in addition to associated genetic factors and that the main therapeutic methods for HMI must be based on the quality of life related to oral health. However, further investigations must be carried out.